Differences in socio-emotional competencies between high-ability students and typically-developing students - Rocha, Alberto; Borges, África; García-Perales, Ramón; Almeida, Ana Isabel S. (Frontiers in Education, 2024)
Social and emotional competencies play a fundamental role in thestudents' comprehensiveoverall development of students. This study aims to analyze possible differences in socio-emotional skills between giftedhigh-abilityies students and students with typical development, using differential quantitative research between subjects. From a sample of 143 students, of whom 51 were identified as giftedhaving high abilities, differences in socio-emotional skills dimensions were explored using a brief self-developed questionnaire to assess their satisfaction with interactions with peers, along with the instrument "For me it is easy": Social and Emotional Skills Assessment Scale for Children and Adolescents. The results indicated that giftedhigh-abilityies schoolchildren exhibited greater dissatisfaction in the choice of friends, the education they received at school, sports and motor skills, and social relationships with friends. The results from the second instrument generally indicated that giftedhigh-abilityies students had lower mean scores in the dimensions evaluated, a difference that was statistically significant in the emotional regulation dimension compared to their typicallydeveloping peers. This study highlights the importance of an inclusive educational approach that considers the specific social-emotional needs of giftedhigh-abilityies students, promoting specific intervention strategies.